Determination of rifampicin in human plasma by high‐performance liquid chromatography coupled with ultraviolet detection after automatized solid–liquid extraction. (5th July 2016) - Louveau, B.; Fernandez, C.; Zahr, N.; Sauvageon‐Martre, H.; Maslanka, P.; Faure, P.; Mourah, S.; Goldwirt, L.
Abstract: A precise and accurate high‐performance liquid chromatography (HPLC) quantification method of rifampicin in human plasma was developed and validated using ultraviolet detection after an automatized solid‐phase extraction. The method was validated with respect to selectivity, extraction recovery, linearity, intra‐ and inter‐day precision, accuracy, lower limit of quantification and stability. Chromatographic separation was performed on a Chromolith RP8 column using a mixture of 0.05 m acetate buffer pH 5.7–acetonitrile (35:65, v/v) as mobile phase. The compounds were detected at a wavelength of 335 nm with a lower limit of quantification of 0.05 mg/L in human plasma. Retention times for rifampicin and 6, 7‐dimethyl‐2, 3‐di(2‐pyridyl) quinoxaline used as internal standard were respectively 3.77 and 4.81 min. This robust and exact method was successfully applied in routine for therapeutic drug monitoring in patients treated with rifampicin.